Functional characterization of variants associated with Familial Hypercholesterolemia - Alves, Ana Catarina (2022)
Familial hypercholesterolemia is a cardiovascular disease risk condition since its characterized by elevated lipid values since childhood. In this work we stratified CVD risk in a sample of FH patients and the general population and analysed both cohorts in terms of lipid lowering therapy used and attainment of lipid therapeutic target levels.